The Construction of Science and the Methodology of Knowledge in the Islamic World - Wahyuni, Teti; Rijal, Syamsul (Universitas Pahlawan Tuanku Tambusai, 2024)
Scientific construction or methodology of knowledge certainly has to do with some understanding of how a person seeks knowledge. Included in it will be mentioned how a person's mind or physical condition in seeking knowledge, aspects that can support a person in sharpening his memory in seeking knowledge and some things that can cause a person's brain to easily forget learning material. The purpose of this article is to revive the concept of scientific order based on some of the classic books of earlier scholars. The research methodology used is a literature review method of summaries of Arabic books that have been translated into Indonesian that have discussed the methodology of science in education. The results of this literature review confirm that the authors of classical books from previous scholars combined educational theory with fiqh and moral studies.